Performances and Rituals for Environmental Campaigns: Structures, Discourses, and Postcolonial Ecocriticism: - Setiawan, Ikwan; Suwargono, Eko; Zamroni, Muhammad; Hartanto, Denny Antyo; Suharto, Suharto (KARSA Journal of Social and Islamic Culture, 2023)
This paper discusses some performing arts and rituals that carry the environmental theme in Jember. Artists and village governments respond creatively to environmental problems by creating several multi-form events, combining performances and certain rituals. We will use postcolonial ecocriticism as a theoretical framework to discuss some of their produced show events. Postcolonial ecocriticism emphasizes analysis to reveal how cultural texts present current ecological problems as a legacy of colonialism in aesthetic works that can function as advocacy and activism. The results of this study show that the performances and rituals develop critical awareness regarding environmental threats and problems in Jember and Indonesia. They bring the topic of the environment to invite the community to jointly maintain the sustainability of the human environment and criticize government policies to legitimize the destruction of nature in the name of development.